2009
DOI: 10.1149/1.3205677
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oxidation Resistance of Fe-Cr Ferritic Alloy Sheets for SOFC Interconnects

Abstract: Fe-Cr ferritic alloys are applied for interconnects of solid oxide fuel cells (SOFCs) operated at around medium temperatures. The oxidation behavior of sheets with various thicknesses of Fe-22%Cr ferritic alloy, ZMG232L, was investigated. The oxidation rate of thin sheet was much higher than that of thick one because Cr content decreased under oxide layer of edge part of thin sheet and therefore Cr oxide became unstable and Fe was mainly oxidized. Such accelerated oxidation behavior was able to be improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The study also found that additions of Cu, from 0.94 wt% to 1.44 wt%, reduced Cr vaporization in alloys containing 0.30 wt% Mn and helped limit growth of the Mn spinel layer. 24 However, Sachitanand et al also studied ZMG 232 G10 steel with Cu additions using the denuder technique described below, but could not reproduce the beneficial effect of Cu on Cr vaporization. 19 Silicon wafer collector.-Another variant to the standard condensation method uses ion-beam analysis to measure the amount of Cr collected on Si wafers during an experiment.…”
Section: Vapor Collection and Analysis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that additions of Cu, from 0.94 wt% to 1.44 wt%, reduced Cr vaporization in alloys containing 0.30 wt% Mn and helped limit growth of the Mn spinel layer. 24 However, Sachitanand et al also studied ZMG 232 G10 steel with Cu additions using the denuder technique described below, but could not reproduce the beneficial effect of Cu on Cr vaporization. 19 Silicon wafer collector.-Another variant to the standard condensation method uses ion-beam analysis to measure the amount of Cr collected on Si wafers during an experiment.…”
Section: Vapor Collection and Analysis Techniquesmentioning
confidence: 99%
“…4,13 In order to gauge the effectiveness of a coating or steel it is necessary to measure the amount of Cr vapor released at SOFC operating temperatures, thus a branch of experimental techniques has emerged to quantify Cr vaporization. [21][22][23][24] The standard approach, known as the transpiration method, enables measurement of chromium vapors in the presence of high concentrations of other gases. 25 Recently, other collection techniques have arisen to avoid some of the challenges posed by the standard transpiration method.…”
mentioning
confidence: 99%
“…Reducing the number of cells increases the current per cell, so it became necessary to further improve the high temperature durability of the ferritic stainless steel material that connects the cells. The degradation modes of the stainless steel used SOFC primarily include the growth of an insulating oxide layer such as Cr2O3, Cr poisoning of the SOFC cathode, 6,7 and anomalous oxidation [8][9][10] due to a decrease in the Cr concentration in the stainless steel. Therefore, high heat resistant ceramic coating is indispensable for the SOFC interconnectors to suppress these degradations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the effect of thickness of sheet of ZMG232L on oxidation behavior was investigated (3). Furthermore, the effect of alloying elements and impurities on oxidation resistance of ZMG232L was investigated and oxidation resistance of thin sheet was able to be improved by reducing Mn, increasing Cr, and adding W in ZMG232L (4,5).…”
Section: Introductionmentioning
confidence: 99%